INFLUENCE OF THE PROCESS IN THE GENERATION OF ACETALDEHYDE ANDRESIDUAL LEVELS IN POLY (ETHYLENE TEREPHTHALATE) (PET) PACKAGINGAND DRINKS- REVIEW ARTICLE - ANJOS, CARLOS ALBERTO RODRIGUES (Revista Brasileira de Engenharia de Biossistemas, 2007)
The main objective of this text is to congregate relative information to the presence of theacetaldehyde, its chemical formation, reactions, forms for which if manifest in drinks and sourcesof contamination proceeding from different ways in the production systems, packaging andenvironment. It is a review of commented and discussed references, where the author inserts itsexperience in technology of PET resin transformation, as well as packaging for diverse conditionedproducts and also theoretical and practical beddings of the related stages of the process to theacetaldehyde formation